EU as a Trade Power: Adjusting Instruments of Foreign Economic Policy - Egor A. Sergeev; Kristina V. Soroka (Современная Европа)
The focus of this study is aimed at the foreign economic policy of the European Union and the areas of its implementation. The article is based on a comprehensive approach to the concept of EU foreign economic policy as a set of instruments combining trade and investment policies of the EU. The study evaluates the communitarization of the main directions of the EU’s foreign economic policy. As a result, it is concluded that the exclusive competence of the supranational bodies of the Union is partially extended to investment policy. Considering that the paradigm of realism is taken as the basis for the study, the subject of the article is to assess the role of the EU’s foreign economic policy in the realization of the Union’s foreign policy interests. The authors believe that the European Union as a “trade power”, seeks not only to achieve economic benefits, but also to ensure that its trading partners meet a number of regulatory and value requirements. Taking into account the transformation of the world order, the need for the European Union to strengthen its own political subjectivity and economic competitiveness is increasing. This leads to the expansion of “defensive” measures in trade policy (sanctions mechanism for non-compliance with the provisions on sustainable development in trade agreements) and investment policy (mechanism for controlling foreign direct investments). As a result, it strengthens the normative and value content of EU foreign economic policy on one hand and make it more protectionist on the other hand. The authors of the article conclude that by means of foreign economic policy, the European Union, as a “trading force”, seeks to create and maintain an international trade order based on rules that are beneficial to the EU.